Three isolate of actinomycetes as biological control against Magnaporthe orzyae and Fusarium solani - Aisyah Fatiha Zailan; Muhammad Asyraff Abd Samad; Anis Farhan Fatimi Ab Wahab; Shazilah Kamaruddin; Quay, Doris Huai Xia; Ahmad Bazli Ramzi; Farah Diba Abu Bakar; Abdul Munir Abdul Murad; Izwan Bharudin (Penerbit Universiti Kebangsaan Malaysia, 2024)
Phytopathogens are causing global food security concerns, resulting in approximately 12.5% crop loss. These fungi significantly impact plant physiology, growth, and development. Traditional fungicides used for control are known to be harmful to both humans and the environment. Therefore, this study advocates an eco-friendly approach using biological control agents to curb phytopathogenic fungi growth. This research focuses on identifying potential antagonistic microorganisms capable of inhibiting two common phytopathogenic fungi: Magnaporthe oryzae, responsible for rice blast disease, and Fusarium solani, causing Fusarium wilt disease. The inhibitory strength of the microorganisms isolated from six different locations in Peninsula Malaysia was tested in vitro via dual culture assays. Our findings revealed three actinomycete species isolated from Bangi Forest Reserve, UKM, namely Streptomyces morookaense UKM1, Streptomyces rubrisoli UKM1, and Streptomyces gelaticus UKM1 exhibit a remarkable ability to inhibit the growth of both M. oryzae and F. solani, with a percentage inhibition radial growth (PIRG) exceeding 70%. Additionally, distinct differences in pathogens mycelia were observed after being grown together with the antagonistic microorganisms. In summary, our research identifies promising microorganisms with potent inhibition capabilities against multiple plant pathogens, offering potential solutions for sustainable agriculture and improved food security.